2012
DOI: 10.1021/la2045493
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Platinum Nanoparticles on Graphene Nanosheets with a Significant Improvement in Stability and CO Tolerance

Abstract: Graphene nanosheets (GNS) supporting Pt nanoparticles (PNs) are prepared using perfluorosulfonic acid (PFSA) as a functionalization and anchoring agent. Transmission electron microscope (TEM) results indicate that the prepared Pt NPs are uniformly deposited on GNS with a narrow particle size ranging from 1 to 4 nm in diameter. A high catalytic activity of this novel catalyst is observed by both cyclic voltammetry and oxygen reduction reaction (ORR) measurements due to the increasing of proton (H(+)) transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 43 publications
3
69
0
Order By: Relevance
“…424 In a recent study, HRG/Pt nanocomposites prepared with perfluorosulfonic acid (PFSA) as functionalization and anchoring agent, were applied as electrocatalyst for ORR. 425 The PFSA not only enhanced the Pt-graphene interactions and the stability of the catalyst, but also provided more channels for H + towards Pt surfaces, thereby creating more active catalytic sites (cf. Fig.…”
Section: Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…424 In a recent study, HRG/Pt nanocomposites prepared with perfluorosulfonic acid (PFSA) as functionalization and anchoring agent, were applied as electrocatalyst for ORR. 425 The PFSA not only enhanced the Pt-graphene interactions and the stability of the catalyst, but also provided more channels for H + towards Pt surfaces, thereby creating more active catalytic sites (cf. Fig.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…The results demonstrated that the graphitic and amino-type of nitrogen components determine the onset potential and electron transfer number, while the total content of graphitic and pyridinic nitrogen atoms is the key factor to enhance the current density in the electrocatalytic activity for ORR. 425 It is clear that graphene-based inorganic nanocomposites show enhanced performance as electrocatalysts in fuel cells compared to the cost-inefficient Pt/C commercial electrocatalysts.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…In many scientific reports graphene oxide (GO) has been used to support Pt nanoparticles, due to oxygen-containing functional groups on both basal planes (epoxy and hydroxyl groups) and edge planes (carbonyl and carboxyl groups). They are usually not single-layer and the presence of oxygen functional groups can act as anchoring sites to attach nanoparticles and enhance the uniform distribution [20,21].…”
Section: Graphenementioning
confidence: 99%
“…For instance, we prepared Na¯on decorated Pt NPs on various supports (e.g., carbon black, carbon nanotube, graphene, nanoceramics, etc. ), [13][14][15][16] which showed much improvement in the ORR mass activity compared to that without Na¯on decoration. However, hitherto, the e®ect of Na¯on on ORR speci¯c is not unknown, and the mechanism of the ÀSO 3 H containing polymer in facilitating the ORR activity remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…8,9 Normally, approaches to improving the ORR activity include integrating Pt with other transition metals (e.g., Pt-Co, Pt-Pd, Pt-Au), 5,10,11 controlling the size of the Pt nanoparticles (NPs) to increase their speci¯c surface areas (e.g., ultrasmall Pt clusters 5 ) and engineering crystal facets to improve catalytic performance (generally the ORR activity obeys a sequence: Pt ð100Þ >Pt ð111Þ >Pt (110) 12 ). In addition, the strategy of decorating the Pt NPs surface with ÀSO 3 À containing polymers [13][14][15][16] (e.g., per°uorosulfonic acid (PFSA), namely Na¯on r Þ or adopting ÀSO 3 À functionalized supports, 17,18 leads to a much enhanced mass activity of ORR as well as an outstanding stability. For instance, we prepared Na¯on decorated Pt NPs on various supports (e.g., carbon black, carbon nanotube, graphene, nanoceramics, etc.…”
Section: Introductionmentioning
confidence: 99%